2020
DOI: 10.3389/fphar.2020.01067
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Pharmacology, Toxicology and Pharmacokinetics of Matrine

Abstract: Matrine (MT) is a naturally occurring alkaloid and an bioactive component of Chinese herbs, such as Sophora flavescens and Radix Sophorae tonkinensis. Emerging evidence suggests that MT possesses anti-cancer, anti-inflammatory, anti-oxidant, antiviral, antimicrobial, anti-fibrotic, anti-allergic, antinociceptive, hepatoprotective, cardioprotective, and neuroprotective properties. These pharmacological properties form the foundation for its application in the treatment of various diseases, such as multiple type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 153 publications
(176 reference statements)
1
41
1
3
Order By: Relevance
“…The second phenanthridine type alkaloid is matrine, a bioactive ingredient of Sophora flavescens and Sophora tonkinensis , two medicinally used plant species in China and many Eastern countries [ 29 , 30 , 31 ]. The compound was found to possess a variety of pharmacological activities comprising different types of cancer [ 29 , 30 , 31 , 32 ]. Same as lycorine, also matrine was used as natural lead compound, also because it is very stable and shows only a few functional groups; therefore, it can be easily modified [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The second phenanthridine type alkaloid is matrine, a bioactive ingredient of Sophora flavescens and Sophora tonkinensis , two medicinally used plant species in China and many Eastern countries [ 29 , 30 , 31 ]. The compound was found to possess a variety of pharmacological activities comprising different types of cancer [ 29 , 30 , 31 , 32 ]. Same as lycorine, also matrine was used as natural lead compound, also because it is very stable and shows only a few functional groups; therefore, it can be easily modified [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Matrine is the main bioactive compound in Kushen and has several pharmacological effects (You et al, 2020;Zhang et al, 2020), such as anti-cancer, anti-oxidant, anti-inflammatory properties. With these pharmacological properties, matrine has been widely used in the treatment of several diseases (You et al, 2020;Zhang et al, 2020), such as cancers, myocardial ischemia, rheumatoid arthritis, and Alzheimer's disease. Considering the wide broad spectrum activities of matrine, whether it affects platelet function and thrombus formation remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, matrine participates in the reversion of multidrug resistance through regulating the expression of several proteins, such as P-glycoprotein (P-gp), multidrug resistancerelated protein (MRP) (Chai et al, 2010;Zhou et al, 2018). Moreover, matrine has anti-inflammatory effects via regulation of the expression of several inflammatory cytokines (such as TNF-α, IL-1) or signaling (such as NF-κB) or the inflammatory mediators (nitric oxide and matrix metalloproteinases) (You et al, 2020). In this study, we showed that matrine also exerts antiplatelet effect as demonstrated by a significant decrease of platelet aggregation, dense granule release, platelet spreading, and clot retraction after matrine treatment compared to vehicle treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ridix Sophorae Flavescentis (Ku Shen), documented in editions of the pharmacopoeia of the People's Republic of China, has had more than 200 compounds isolated and extracted. Modern pharmacological studies have shown that matrine is the most active of these components with multiple pharmacological effects, including anti-tumor, antiviral, and antiinflammation, as well as anti-asthmatic activities (Wang et al, 2015a;You et al, 2020). The main target of matrine's anti-tumor therapeutic effects is to induce autophagic cell death and apoptosis in the cancer cells.…”
Section: The Single Herbs In Modulating Autophagymentioning
confidence: 99%